STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Putra, Joni; Hendriani, Suswati (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
Educational institutions will run effectively if they are organized by school principals and teachers who have professional competence in carrying out their duties. Principal leadership plays an important role in determining the professional competence of a teacher. Therefore, this study aims to describe the principal's leadership strategy in increasing the professional competence of teachers at SDN 03 Tanjung Balik, X Koto Diatas District, Solok Regency. The methodology used in this study is a qualitative descriptive method in the form of a case study. The subjects of this study were the principal and all teachers at SDN 03 Tanjung Balik. The research instruments are interview guides, observation and documentation. The results of this study indicate that there are 6 principal leadership strategies in improving the professional competence of teachers at SDN 03 Tanjung Balik, namely 1) Carrying out upgrading activities for teachers continuously, 2) cultivating literacy activities, 3) increasing the use of learning media, 4) improving facilities infrastructure in learning, 5) Conduct supervision activities.